2003
DOI: 10.1148/radiol.2283020322
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Hematopoietic Progenitor Cells with MR Contrast Agents

Abstract: Hematopoietic progenitor cells can be labeled with MR contrast agents and can be depicted with a standard 1.5-T MR imager.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
161
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(172 citation statements)
references
References 25 publications
8
161
0
3
Order By: Relevance
“…In this study, we did not perform additional investigations of the cell function before and after the labeling procedure. In previous studies, we investigated the function of hematopoietic cells more extensively and did not find any impairment of the cells due to our labeling procedure (26,39). This is in accordance with data from the literature (17,20,22,25,(40)(41)(42).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we did not perform additional investigations of the cell function before and after the labeling procedure. In previous studies, we investigated the function of hematopoietic cells more extensively and did not find any impairment of the cells due to our labeling procedure (26,39). This is in accordance with data from the literature (17,20,22,25,(40)(41)(42).…”
Section: Discussionsupporting
confidence: 91%
“…14 Here we used Effectene to transfect the MRI contrast agent Gd-DTPA into stem cells, because it is relatively more efficient and less toxic than liposome, calcium phosphate, or viral vectors for transfection into primary cells. [15][16][17] There was a possibility that phagocytosed or dead transplanted cells with Gd-DTPA were detected by the MRI. However, a previous pharmacokinetic study reported that Gd-DTPA in dead cells or interstitial spaces was washed out within 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced detection of bone marrow is possible through SPIO 27,61 and possibly SSPIO, such as AMI-25 as well. 146 Bone marrow lesions are usually detected with high sensitivity, except in the complicating cases of children and 117 adults with red marrow hyperplasia.…”
Section: Cancer Imagingmentioning
confidence: 99%
“…The cells were Internalizing cell surface receptor-mediated endocytosis of SPIO is another avenue through which cell migration can be observed in vivo. 27 Bulte and coworkers utilized anti-transferrin receptor antibodies conjugated to nanoparticles in order to observe oligodendrocyte migration postneurotransplantation. 19 The SPIO did not interfere with the cells' ability to myelinate in vivo, and histological evaluation of the cells with nanoparticles revealed cell migration up to 10 mm in 14 days.…”
Section: Cell Trackingmentioning
confidence: 99%